Rain on the roof - Scott, Janine; Forss, Ian (Minneapolis, Minn. : Picture Window Books, 2005)
When the farmhouse roof begins to leak, Farmer Claude and Farmer Maude seek shelter in the shed with the animals, but when that roof leaks, too, they all head for the truck.
13 26 29 31
Keywords: Farmers -- Fiction; Rain and rainfall -- Fiction; Domestic animals -- Fiction; Stories in rhyme